Propagation of Meteorological to Hydrological Droughts in India. Issue 22 (14th November 2020) - Bhardwaj, Kunal; Shah, Deep; Aadhar, Saran; Mishra, Vimal
Abstract: Drought is among the costliest natural disasters that affect the economy, food and water security, and socioeconomic well‐being of about 1.4 billion people in India. Despite the profound implications of droughts, the propagation of meteorological to hydrological droughts in India is not examined. Here, we use observations and simulations from a well‐calibrated and evaluated Variable Infiltration Capacity (VIC) model to estimate drought propagation in India. Standardized Precipitation Index (SPI), Standardized Soil Moisture Index (SSMI), and Standardized Streamflow Index (SSI) were estimated for 223 catchments in India to represent meteorological, agricultural, and hydrological droughts, respectively. We estimated drought propagation time for these catchments located in 18 major Indian subcontinental river basins. Internal propagation of hydrological drought was estimated using optimal hydrological Instantaneous Development Speed (IDS) and Instantaneous Recovery Speed (IRS) from onset to the termination. Indus, Sabarmati, and Godavari river basins have higher propagation time of meteorological to hydrological droughts. The high (low) development rate of hydrological drought is followed by the high (low) recovery rate for most of the locations. We find significant influence of Seasonality Index (SI) and Base Flow Index (BFI) on propagation time of meteorological to hydrological droughts in the Indian subcontinental river basins. Overall, understanding of drought propagation, development/recovery speed, and their deriving factors can assist in the management and planning of water resources in India. Key Points: Drought propagation was estimated using SPI and the VIC model‐simulated SSI at 223 locations in the Indian subcontinent Indus, Sabarmati, and Godavari river basins have longer drought propagation times A majority of catchment characteristics do not show a strong relationship with drought parameters